A new species of Arthromelodes Jeannel from Okinawa-jima, Japan (Coleoptera, Staphylinidae, Pselaphinae) - Jałoszyński, Paweł (Zootaxa, 2023)
To date, twenty species and subspecies of Arthromelodes Jeannel were known to occur in Japan, distributed in Honshȗ, Kyȗshȗ, Shikoku, Yakushima, and Amami Islands. No species have been recorded from central or southwestern Ryȗkyȗ. Arthromelodes tokushigei sp. n., the first species known to inhabit Okinawa Island of the central Ryȗkyȗ is described. This wingless species seems to be restricted to the northern Yambaru forest of Okinawa. In order to facilitate future studies on Arthromelodes and related, poorly-defined genera of Batrisini, detailed morphological documentation of the new species is provided.